Pathogenesis of Minimal Change Nephrotic Syndrome: A Review of the Underlying Molecular Mechanisms - Yang, Eun Mi (Childhood kidney diseases, 2019)
Nephrotic syndrome (NS) is the most common glomerular disorder in childhood, and a vast majority of cases are idiopathic. The precise cause of this common childhood disease is not fully elucidated despite significant advancements in our understanding of podocyte biology. Idiopathic NS has been considered “a disorder of T-cell function” mediated by a circulating factor that alters podocyte function resulting in massive proteinuria since the last four decades. Several circulatory factors released from T-cells are considered to be involved in pathophysiology of NS; however, a single presumptive factor has not been defined yet. Extended evidence obtained by advances in the pathobiology of podocytes has implicated podocytes as critical regulator of glomerular protein filtration and podocytopathy. The candidate molecules as pathological mediators of steroid-dependent NS are CD80 (also known as B7-1), hemopexin, and angiopoietin-like 4. The “two-hit” hypothesis proposes that the expression of CD80 on podocytes and ineffective inhibition of podocyte CD80 due to regulatory T-cell dysfunction or impaired autoregulation by podocytes results in NS. Recent studies suggest that not only T cells but also other immune cells and podocytes are involved in the pathogenesis of MCNS.